Characteristics analysis of digital image‐plane holographic microscopy. Issue 4 (3rd September 2015) - Zeng, Yanan; Chang, Xinyu; Lei, Hai; Hu, Xiaodong; Hu, Xiaotang
Summary: We utilize digital image‐plane holographic microscopy (DIPHM) to achieve the real‐time surface profile measurement of microstructure. The impulse response functions of DIPHM and traditional digital holographic microscopy (DHM) are both derived. The theoretical derivations indicate that the differences between the two techniques are caused by the diffraction effect of the recording plane with a finite size. The diffraction effect would introduce an unstable factor to the wavefront reconstruction. Therefore, the DIPHM has the characteristics of totally full field of view and low measuring noise compared to DHM. In addition, we take DIPHM and DHM in dual‐wavelength mode as a special example to confirm the points above. From both experimental results and theoretical analysis, DIPHM is demonstrated to be an optimized technique with high‐quality imaging, especially benefiting the situation where multi‐wavelength measurement is required. This method is robust against environmental noise. SCANNING 38:288–296, 2016. © 2015 Wiley Periodicals, Inc.